Condition monitoring of distribution transformer's mechanical parts using sweep frequency response analysis (SFRA) - Ghani S.A.; Thayoob Y.H.M.; Ghazali Y.Z.Y.; Khiar M.S.A.; Chairul I.S. (Elsevier Ltd, 2023)
Distribution transformer is the key element in the electricity transmission throughout the nation. Hence, serious attention for the transformer condition monitoring is a crucial. With an occurrence of short-circuit in the power system, the transformer active parts such as core and winding will experience a mechanical movement created by the electromagnetic forces. There are various types of transformer condition monitoring measurement in market, but the monitoring of the mechanical movement in transformer is still lacking. Therefore, Sweep Frequency Response Analysis (SFRA) has been introduced to assess any mechanical movement especially of the transformer's core and winding. The frequency response of the transformer provides mechanical information of core and winding conditions. The SFRA measurement results were validated using the actual transformer untanking process. 2013 The Authors. Published by Elsevier.